Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T19:14:54+01:00
C)
2(x-1)+3(x+1) = 26
2x-2+3x+3 = 26
5x+1 = 26
5x = 26-1
5x = 25 |:5
x = 5

d)
4(3-x)+9 = 7(2+x)+29
12-4x+9 = 14+7x+29
21-4x = 43+7x
-4x-7x = 43-21
-11x = 22 |:(-11)
x = -2

e)
2(x-3)+3(x-4)+4(x-5) = 0
2x-6+3x-12+4x-20 = 0
9x-38 = 0
9x = 38 |:9
x = 4i2/9
2010-03-17T19:17:15+01:00
C)2x-2+3x+3=26
5x=26+2-3
5x=25 /:5
x=5

d)12-4x+9=14+7x+29
-11x=22 /:(-11)
x=-2

e)2x-6+3x-12+4x-20=0
9x=38 /:9
x= 6 i 2/9
2010-03-17T19:18:32+01:00
2(x-1)+3(x+1)=26
2x-2+3x+3=26
5x=26-3+2
5x=25/:5
x=5

4(3-x)+9=7(2+x)+29
12-4x+9=14+7x+29
-4x-7x=-12-9+14+29
-11x=22/:(-11)
x=2

2(x-3)+3(x-4)+4(x-5)=0
2x-6+3x-12+4x-20=0
9x=38/:9
x=38/9=4 i2/9